Transfusion Reaction among the Blood Recipient - A Study of 120 Cases (Journal of Dhaka Medical College, 2010)
Context: Blood transfusion is a life saving procedure. Transfusion of one unit of blood, plasma or platelet if employed safely, well in time with proper intensive care can save many valuable lives. But due to transfusion a number of untoward reactions develop that are sometimes more serious and life threatening So the aim of this study was to find out the most frequent and life threatening reactions that develop during transfusion.Methods: In between January'2006 to December'2007 a total 120 subjects, mean aged 25.9 ±13.9 years were selected as study population in BSMMU. Those who were receiving transfusion for congenital hemolytic anemia, aplastic anemia, refractory anaemia, undiagnosed anaemia, anaemia of chronic disease, hematological malignancy, post chemotherapy, clotting factor deficiency, pre and post operatively as well as during operation. The transfusion unit was single unit to 100 unit of fresh whole blood or its component- red cell concentrate, fresh frozen plasma, platelet concentrate, cryoprecipitate.Results: There were 8 (6.66%) patients showed reactions of different types. Among them febrile reaction was 5 (62.5%), allergic reaction was 2 (25%) and 1 (12.5%) developed pulmonary congestion (Transfusion Related Acute Lung Injury), characterized by cough, shortness of breath and increase rate of respiration. No fatal reaction observed during the study period. Key words: Transfusion reaction; Febrile reaction; Allergic reaction. DOI: 10.3329/jdmc.v17i2.6585J Dhaka Med Coll. 2008; 17(2) : 67-71